2006
DOI: 10.1158/0008-5472.can-06-1500
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Is an AMP Kinase–Dependent Growth Inhibitor for Breast Cancer Cells

Abstract: Recent population studies provide clues that the use of metformin may be associated with reduced incidence and improved prognosis of certain cancers. This drug is widely used in the treatment of type 2 diabetes, where it is often referred to as an ''insulin sensitizer'' because it not only lowers blood glucose but also reduces the hyperinsulinemia associated with insulin resistance. As insulin and insulin-like growth factors stimulate proliferation of many normal and transformed cell types, agents that facilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
483
5
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 951 publications
(536 citation statements)
references
References 23 publications
26
483
5
7
Order By: Relevance
“…These results are emphasized by the fact that the antidiabetic drug inhibited S6K1 phosphorylation in the absence of the two catalytic units of AMPK suggesting that the antiproliferative effect of metformin are mediated through the mTOR pathway independently of AMPK. Our study contradicts the results obtained in MCF-7 by Zakikhani et al (2006) who showed that metformin inhibits cell growth via the a1 AMPK subunit in MCF-7 breast cancer cells. This disparity may be due to a cell specific effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are emphasized by the fact that the antidiabetic drug inhibited S6K1 phosphorylation in the absence of the two catalytic units of AMPK suggesting that the antiproliferative effect of metformin are mediated through the mTOR pathway independently of AMPK. Our study contradicts the results obtained in MCF-7 by Zakikhani et al (2006) who showed that metformin inhibits cell growth via the a1 AMPK subunit in MCF-7 breast cancer cells. This disparity may be due to a cell specific effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent data suggest that metformin could protect from cancer (Schneider et al, 2001;Evans et al, 2005) and inhibit breast and glial cancer cell proliferation in vitro (Zakikhani et al, 2006). Here we show that metformin not only is a very potent inhibitor of human prostate cancer cell growth, but also inhibits tumorigenesis in a xenograft model when it is administrated orally or i.p.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It will be of interest to determine whether this protective effect of Lkb1-AMPK signaling involves systemic metabolic effects, metabolic effects in evolving tumor cells, maintenance of cell polarity, or a combination of these processes. Recent data suggest that this pharmacological activation of AMPK may also be beneficial for treatment of established tumors with intact Lkb1-AMPK-TSC signaling, as metformin slows proliferation of cancer cell lines (Zakikhani et al, 2006).…”
Section: Mechanisms Of Neoplastic Suppressionmentioning
confidence: 99%
“…In addition, an AMPK-independent, rag GTPasedependent pathway by which metformin inhibits mammalian target of rapamycin complex 1 has recently been described (Kalender et al, 2010). By decreasing mitochondrial ATP production, metformin can indirectly activate LKB1-AMPK signaling in vitro in transformed cells, with consequences including inhibition of protein synthesis (Dowling et al, 2007), proliferation (Zakikhani et al, 2006 and expression of fatty acid synthase (Algire et al, 2010).…”
Section: Introductionmentioning
confidence: 99%